EGFR-Mutant Non-small Cell Lung Cancer: State-of-the-Art and Future Perspectives - Antonio Rossi; Ettore Mari (European Medical Journal)
EGFR mutations are the first identified targetable driver alterations in advanced non-small cell lung cancer (NSCLC), for which specific epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKI) have been developed. These small molecules, administered orally, changed the natural history of patients with EGFR-mutated NSCLC, reporting impressive response and survival data. Osimertinib, a third-generation EGFR-TKI, can be considered the standard first-line therapy for the ‘common’ EGFR mutations, which include the exon 19 deletion and Leu858Arg point mutation in exon 21, accounting for 90% of cases. The ‘uncommon’ EGFR mutations, highly heterogeneous and with a low frequency, seem to be more sensitive to afatinib and osimertinib, a second-generation EGFR-TKI, excluding the EGFR exon 20 insertions mutations, for which a platinum-based regimen should be recommended while waiting for specific targeted inhibitors to reach the market. However, after an initial activity to first-line EGFR-TKI treatment, a disease progression is reported due to the presence of an intrinsic resistance or the onset of an acquired resistance. The latter can be broadly grouped into EGFR-dependent or EGFR-independent mechanisms of resistance, for which several new drugs and strategic approaches are under investigation. This review focuses on the state-of-the-art EGFR-TKIs in the treatment of metastatic NSCLC harbouring EGFR mutations, and also discusses potential future perspectives.